Pengembangan Media Visual Kola pada Peserta Didik Kelas 1 SD Negeri I Puhpelem - Dewi Lestari; Suharno Suharno; Benny Agus Pribadi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
The Objective Of The Research Is: (1) describe the steps of developing KOLA visual media (2) to test the effectiveness of KOLA visual media. (3) To find out the increase in the ability to arrange a collection of objects based on patterns in class 1 students. The type of research is development research. The research was conducted at the Budi Utomo Cluster Elementary School, Puhpelem District, Wonogiri Regency. Data collection techniques with tests, non-tests and interviews. Test the effectiveness of the product using the after-before experiment and the mean difference test. The results showed that the KOLA visual media was effective to be used as a learning medium. KOLA visual media is effectively used in learning mathematics. There is a difference in the ability to arrange a collection of objects based on patterns between students who are taught using KOLA visual media and students who are not taught using KOLA visual media.